2019
DOI: 10.3390/ijms20143512
|View full text |Cite
|
Sign up to set email alerts
|

Social Defeat Modulates T Helper Cell Percentages in Stress Susceptible and Resilient Mice

Abstract: Altered adaptive immunity involving T lymphocytes has been found in depressed patients and in stress-induced depression-like behavior in animal models. Peripheral T cells play important roles in homeostasis and function of the central nervous system and thus modulate behavior. However, the T cell phenotype and function associated with susceptibility and resilience to depression remain largely unknown. Here, we characterized splenic T cells in susceptible and resilient mice after 10 days of social defeat stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 69 publications
2
11
0
1
Order By: Relevance
“…Specifically, mesenteric lymph node cells from mice exposed to chronic circadian misalignment show increased differentiation of IL-17A + Th17 cells (Inokawa et al, 2020). Although effects of acute SD on adaptive immunity are not well characterized, exposure of male C57BL/6J mice to repeated SD by a larger, dominant male CD1 mouse results in increases in splenic IL-17-producing CD4 + and CD8 + T cells and reduced Treg in stress-susceptible mice, relative to control mice, as defined by the social interaction ratio in a social interaction test (Ambrée et al, 2019). These data are in turn consistent with previous studies demonstrating that development of learned helplessness in mice is dependent on increased Th17 responses, through RORγt-and IL-17A-dependent mechanisms (Beurel et al, 2013).…”
Section: Effects Of M Vaccae Nctc 11659 On the Host Brainstem Serotomentioning
confidence: 99%
“…Specifically, mesenteric lymph node cells from mice exposed to chronic circadian misalignment show increased differentiation of IL-17A + Th17 cells (Inokawa et al, 2020). Although effects of acute SD on adaptive immunity are not well characterized, exposure of male C57BL/6J mice to repeated SD by a larger, dominant male CD1 mouse results in increases in splenic IL-17-producing CD4 + and CD8 + T cells and reduced Treg in stress-susceptible mice, relative to control mice, as defined by the social interaction ratio in a social interaction test (Ambrée et al, 2019). These data are in turn consistent with previous studies demonstrating that development of learned helplessness in mice is dependent on increased Th17 responses, through RORγt-and IL-17A-dependent mechanisms (Beurel et al, 2013).…”
Section: Effects Of M Vaccae Nctc 11659 On the Host Brainstem Serotomentioning
confidence: 99%
“…[ 100 ] For instance, CSDS (which tends to be immunosuppressive) is characterized by a specific pattern of peripheral T cell responses associated with social defeat. [ 101 ]…”
Section: Microglia Transduce Environmental Influences Into Developmenmentioning
confidence: 99%
“…Finally, the article by Ambrée et al examining mechanistic aspects of the T cell response in stress-induced depression-like behavior [7] is outlined in the next section on animal models in more detail.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Ambrée and colleagues used social defeat stress (SDS) as a model for stress-induced depression-like behavior to shed light on the T cell phenotype associated with susceptibility and resilience to depression [7]. The authors grouped SDS-exposed mice into susceptible and resilient and found significantly increased numbers of interleukin-17 producing CD4+ and CD8+ T cells in the spleen of susceptible mice.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation